THE ROLE OF RW IN SUSTAINABLE WASTE MANAGEMENT (CASE STUDY OF PERUMAHAN TAS 4 REGENCY, JAMBANGAN VILLAGE) - Baskoro, Deny Indra; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the role of the Gardenia Lestari Waste Bank, established on 19 October 2019, in enhancing environmental awareness, improving waste management efficiency, increasing community participation, and generating economic benefits in RW 8. Method: A qualitative descriptive approach was employed to gain an in-depth understanding of the institution’s functions. Data were collected through in-depth interviews with administrators and residents, participatory observations of waste management activities, and documentation analysis of waste collection records over time. Results: The findings indicate that the Gardenia Lestari Waste Bank serves not only as an organized system for waste collection and recycling but also as a community-based educational platform that effectively promotes environmental awareness. Through community engagement and consistent socialization strategies, the institution has demonstrated significant environmental improvements while generating financial benefits from the sale of recyclable materials. Novelty: This study provides empirical insights into the dual role of waste banks as both environmental management institutions and agents of social change, highlighting a sustainable, community-driven model for addressing environmental challenges at the local level.